Searching for the apprehension of the past in Flaubert’s Parrot by Julian Barnes - Silva, Maria das Graças Gomes Villa da (ITINERÁRIOS – Revue de Littérature, 2010)
In Flaubert’s Parrot, by Julian Barnes, the narrator-protagonist is seduced by the question: how do we know the past? It is from this question that this narrative is studied based on the Freudian studies. The aim is to show the narrator’s work to demonstrate that the past representation taken as an unchangeable truth is impossible.